Evaluation of antioxidant and cytotoxicity activities of copper ferrite (CuFe2O4) and zinc ferrite (ZnFe2O4) nanoparticles synthesized by sol-gel self-combustion method - Kanagesan, Samikannu; Hashim, Mansor; Ab. Aziz, Sidek; Ismail, Ismayadi; Subramani, Tamilselvan; Mohammed Alitheen, Noorjahan Banu; Swamy, Mallappa Kumara; Rao, Bandaru Purna Chandra (MDPI, 2016)
Spinel copper ferrite (CuFe2O4) and zinc ferrite (ZnFe2O4) nanoparticles were synthesized using a sol-gel self-combustion technique. The structural, functional, morphological and magnetic properties of the samples were investigated by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Transmission electron microscopy (TEM) and vibrating sample magnetometry (VSM). XRD patterns conform to the copper ferrite and zinc ferrite formation, and the average particle sizes were calculated by using a transmission electron microscope, the measured particle sizes being 56 nm for CuFe2O4 and 68 nm for ZnFe2O4. Both spinel ferrite nanoparticles exhibit ferromagnetic behavior with saturation magnetization of 31 emug-1 for copper ferrite (50.63Am2/Kg) and 28.8 Am2/Kg for zinc ferrite. Both synthesized ferrite nanoparticles were equally effective in scavenging 2,2-diphenyl-1-picrylhydrazyl hydrate (DPPH) free radicals. ZnFe2O4 and CuFe2O4 nanoparticles showed 30.57% ± 1.0% and 28.69% ± 1.14% scavenging activity at 125 μg/mL concentrations. In vitro cytotoxicity study revealed higher concentrations (> 125 μg/mL) of ZnFe2O4 and CuFe2O4 with increased toxicity against MCF-7 cells, but were found to be non-toxic at lower concentrations suggesting their biocompatibility.